The launch of the Pacific vector network: connecting Pacific Island Countries and areas to prevent and control vector-borne diseases - Limb K. Hapairai; Salanieta T. Saketa; Amandeep Singh; Rosanna Y. Rabago; Amanda K. Murphy; Tessa B. Knox; Nuha Mahmoud; Emi Chutaro; Anna Drexler; Pacific Vector Network contributors (Parasites & Vectors)
Abstract The Pacific Island Health Officers’ Association, the World Health Organization, and the Pacific Community co-organized the launch of the Pacific Vector Network (PVN) to address challenges posed by mosquito-borne diseases, including dengue fever, Zika virus disease, chikungunya, malaria, and lymphatic filariasis. The PVN was created as a new initiative under the Pacific Public Health Surveillance Network (PPHSN). This launch was a critical step in the build-up to PVN as a full-service network of PPHSN in the coming years. The Pacific Island Countries and areas (PIC)-led network comprises vector management leadership, officers, and technical partners dedicated to supporting information-sharing to promote evidence-based collective action and innovation. The setup of a Technical Working Body to ensure governance and to steer forward the work of the network was a key deliverable. This manuscript describes the proceedings and discussions of PIC representatives and several regional partners at the inaugural PVN meeting held 5–7 June 2023 in Hawai’i, USA. Graphical Abstract